Utilization of microorganism on the development of halal food based on biotechnology - Hayyun Durrotul Faridah; Silvi Kurnia Sari (Universitas Airlangga, 2019)
Biotechnology has rapidly developed until now. The use of biotechnology was very extensive for human needs, including the food industry. Some biotechnological processes, both conventional modern, were inseparable from the use of microorganisms. A number of certain microorganisms were used in traditional food through fermentation such as yogurt, tape, cheese and salted vegetables. In addition, microorganisms also used in the DNA recombination process to produce high quality food products such as GMO (Genetically Modified Organism). Indonesia is a country with a majority of the Muslim population so that in the provision of food was very concerned about aspects of halal. Included in biotechnology foods that utilizing microorganism and have to pay attention of the halal critical point. In this case, needs to be considered so that every production process can be ensured to avoid contamination of non-halal materials